PERAN TEKNOLOGI DIGITAL DALAM PENERAPAN ENTREPRENEURSHIP PENDIDIKAN DI ERA DIGITAL - Rizqi Nur Amalya; Lu'lu 'Aabidah; M.Iqodzul Himam Abil Izz; Zalfaa Zayyana; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has brought significant changes to the world of education, including the implementation of educational entrepreneurship. This article aims to examine the role of digital technology in supporting educational entrepreneurship in the digital era and identify opportunities, challenges, and implementation strategies. The study employed a library research method, reviewing various journal articles, books, and relevant scientific sources. The results indicate that digital technology plays a role in expanding access to entrepreneurship learning, encouraging creativity and innovation, developing a generation of technopreneurs, expanding collaborative networks, and providing more contextual entrepreneurial practical experiences. However, its implementation still faces various challenges, such as gaps in technology access, low digital literacy, high digital business competition, the need for curriculum adaptation, and data security risks. Therefore, an integrated strategy is needed through strengthening the entrepreneurship curriculum, utilizing digital media, project-based learning, and collaboration with the business world. With proper management, digital technology can be a strategic tool in developing a creative, innovative, independent, and competitive generation in the digital era.